CHILD MALIGINE OSTEOPETROSIS: A PURPOSE OF A CASE AND REVIEW OF THE LITERATURE: OSTEOPETROSIS MALIGNA INFANTIL: A PROPÓSITO DE UN CASO Y REVISIÓN DE LA LITERATURA - Aranzábal Alegría, Germán (2019)
Osteopetrosis comprises a series of rare genetic conditions that produce an imbalance in bone remodeling due to abnormal osteoclastic activity. We report a female patient 1 year 4 months, diagnosed with malignant osteopetrosis neuropathic child while causing paleness, distended abdomen with collateral circulation and growth retardation and developmental milestones are investigating. Examination right eye with retinopathy. Skeletal x-rays revealed a generalized bone hyperdensity. She bone marrow aspirate showed hypercellularity with hyperplastic erythroid, megakaryocytic normal white series. Diagnosis was confirmed by clinical and radiological features. The patient received supportive care. While the diagnosis is simple OPAR this is often delayed by the rarity of the disease and the lack of clinical suspicion, early diagnosis and treatment of bone marrow transplant is curative approach to a disease of poor prognosis.